Sensible or Outdated? Gender and Opinions of Tenure Criteria in Canada - Dengate, Jennifer; Farenhorst, Annemieke; Peter, Tracey (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2019)
The university reward structure has traditionally placed greater value on individual research excellence for tenure and promotion, influencing faculty’s allocation of time and definition of worthwhile labour. We find gender differences in Canadian natural sciences and engineering faculty’s opinions of the traditional criteria for measuring academic success that are consistent with an implicit gender bias devaluing service and teamwork. Most women recommend significant changes to the traditional model and its foundation, while a substantial minority of men support the status quo. However, this comparative qualitative analysis finds more cross-gender similarities than differences, as most men also want a more modern definition of success, perceiving the traditional model to be disproportionately supportive of one type of narrow research scholarship that does not align with the realities of most faculty’s efforts. Thus, this study suggests a discrepancy between traditional success criteria and faculty’s understanding of worthwhile labour.